Active Tumor-Targeting Nano-formulations Containing Simvastatin and Doxorubicin Inhibit Melanoma Growth and Angiogenesis - Negrea, Giorgiana; Rauca, Valentin-Florian; Meszaros, Marta Szilvia; Patras, Laura; Luput, Lavinia; Licarete, Emilia; Toma, Vlad-Alexandru; Porfire, Alina; Muntean, Dana; Sesarman, Alina; Banciu, Manuela (Frontiers in Pharmacology, 2022)
Primary melanoma aggressiveness is determined by rapid selection and growth of cellular clones resistant to conventional treatments, resulting in metastasis and recurrence. In addition, a reprogrammed tumor-immune microenvironment supports melanoma progression and response to therapy. There is an urgent need to develop selective and specific drug delivery strategies for modulating the interaction between cancer cells and immune cells within the tumor microenvironment. This study proposes a novel combination therapy consisting of sequential administration of simvastatin incorporated in IL-13-functionalized long-circulating liposomes (IL-13-LCL-SIM) and doxorubicin encapsulated into PEG-coated extracellular vesicles (PEG-EV-DOX) to selectively target both tumor-associated macrophages and melanoma cells. To this end, IL-13 was conjugated to LCL-SIM which was obtained via the lipid film hydration method. EVs enriched from melanoma cells were passively loaded with doxorubicin. The cellular uptake of rhodamine-tagged nano-particles and the antiproliferative potential of the treatments by using the ELISA BrdU-colorimetric immunoassay were investigated in vitro. Subsequently, the therapeutic agents were administered i.v in B16.F10 melanoma-bearing mice, and tumor size was monitored during treatment. The molecular mechanisms of antitumor activity were investigated using angiogenic and inflammatory protein arrays and western blot analysis of invasion (HIF-1) and apoptosis markers (Bcl-xL and Bax). Quantification of oxidative stress marker malondialdehyde (MDA) was determined by HPLC. Immunohistochemical staining of angiogenic markers CD31 and VEGF and of pan-macrophage marker F4/80 was performed to validate our findings. The in vitro data showed that IL-13-functionalized LCL were preferentially taken up by tumor-associated macrophages and indicated that sequential administration of IL-13-LCL-SIM and PEG-EV-DOX had the strongest antiproliferative effect on tumor cells co-cultured with tumor-associated macrophages (TAMs). Accordingly, strong inhibition of tumor growth in the group treated with the sequential combination therapy was reported in vivo. Our data suggested that the antitumor action of the combined treatment was exerted through strong inhibition of several pro-angiogenic factors (VEGF, bFGF, and CD31) and oxidative stress-induced upregulation of pro-apoptotic protein Bax. This novel drug delivery strategy based on combined active targeting of both cancer cells and immune cells was able to induce a potent antitumor effect by disruption of the reciprocal interactions between TAMs and melanoma cells.